Exploring the Experience of Student Researchers and Family Partners Working as an Interdisciplinary Team - Karsten Berg; Mariana dos Santos Ribeiro; Hadiya Huijer; Sandi Whitford; Schroder Sattar; Roslyn M. Compton (SAGE Publishing, 2024)
Introduction Many institutions seek to engage postsecondary students in research to grow future researchers. Despite this common goal, the means to achieve that end is often unknown creating difficulties for students as they seek out research opportunities. Objective This article will share first-hand reports on the experiences of graduate students, undergraduate students, and family partners following their engagement as an interdisciplinary research team. Methods This is a qualitative study using individual open-ended interviews with undergraduate students, graduate students, and patient family partners. The research was conducted using a Patient-Oriented Research approach. The transcripts were analyzed inductively by using Braun and Clarke's six phases of reflexive thematic analysis. Results Two themes were developed from the analysis. The theme of Benefits & Facilitators was developed based on the many positive thoughts, feelings, resiliency, and learning expressed by the students and family partners. The undergraduate students found the experience of "doing" research fulfilling and a great tool for learning how to better use research in practice. Within the second theme Perceived Hierarchy , undergraduate students described themselves as helpers, not responsible, and they did not have the power to make decisions. Conclusion Given the challenges identified in this study, future efforts in this approach should carefully consider the culture and how to best engage graduate students, undergraduate students, and family partners in research teams.